PENGARUH METODE PROYEK TERHADAP PERILAKU SOSIAL ANAK USIA 5-6 TAHUN DI PAUD PANDU PERTIWI KECAMATAN" - Narita, Nanda; R, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This"study aims to determine the effec"of the project "ethod on the" social behavior"of children aged 5-6 years"at PAUD Pandu Pertiwi, Teluk Keramat District."The research method used is"an experimental method"with a"quantitative"research from. The subject"in this study were children aged 5-6 years in class B1"PAUD Pandu Pertiwi Teluk Keramat District, which were determined using a purposive sampling technique."The data collection tool"uses observation sheets and documentation which is then analyzed."The results showed that there was an effect"after the project method was applied to"the social" behavior of chlidren"aged 5-6 years at"PAUD Pandu Pertiwi, Teluk Keramat District."This can be seen from the average"social behavior of"children before and after"the application of the project method is from 1,17 to 1,23. Which means that the social behavior of children has increased."This is also"proven"from the results of hypothesis testing"obtained t_(hitung ) t_(tabel ), namely 3.225 2.160 then H_0rejected and H_a accepted. So the results and conclusions show"that the"project method influences the social behavior"of children aged 5-6 years"in PAUD Pandu Pertiwi, Teluk Keramat District.